Linking Family-Supportive Supervision To Perfomance: The Mediating Role Of Work-Life Balance - Cahyani, Ardelia Regita; Umam, Moh Rifqi Khairul (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The phenomenon of a high number of factory workers is now a trend that offers an instant way to secure a job, including in the Boyolali district. Becoming a worker, especially as a laborer, certainly has its challenges for the perpetrators. Many factors influence a laborer's work performance, one of which is the support of their superiors. The purpose of this study is to analyze the variables examined, including family-supportive supervisor behavior, work performance, and work-life balance. The sample in this study was factory workers who worked in the Boyolali district for a minimum of 3 (three) months. The population in this study is not definitively known. The final number of respondents obtained was 112, which were then processed using the Non-Probability sampling quantitative research method with a purposive sampling technique. The data collection method was through the distribution of questionnaires. The scale used was the Likert scale. The data were processed using the SEM-PLS analysis tool within the structural equation modeling (SEM) framework. The results of this study revealed that family-supportive supervisor behavior is associated with a 0.195 effect on work performance. Work-life balance has a significant effect on work performance, with a correlation coefficient of 0.415. Family supportive supervisor behavior is stated to affect the work-life balance of 0.760. Work-life balance significantly mediates the effect of family supportive supervisor behavior on work performance.